Penentuan umur simpan keripik buah dengan metode accelerated shelf life test model kadar air kritis: Determination of the shelf life of fruit chips using the accelerated shelf life test model critical water content - Ramanda, Muhammad Rizky; Nasution, Syahrizal; Rahmadi, Isnaini; Munawaroh, Nina Lutfia (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2023)
Fruit chips in Darsa Small and Medium Industry at Lampung products do not include an expiry date on the packaging label as important information that consumers must know. This study aims to estimate the shelf life of jackfruit, pineapple and banana chips using the Accelerated Shelf Life Test (ASLT) method with the Labuza equation critical moisture content approach model. The research was conducted by determining the initial water content, critical water content and equilibrium moisture content with other supporting variables such as packaging permeability, slope (b), product solid weight and packaging area. Based on the research results, the initial water content and critical water content of each fruit chips were 0.0348 and 0.0582 gH2O/g solid for jackfruit chips, 0.0348 and 0.0493 gH2O/g solid for pineapple chips, 0.0525 and 0.0741 gH2O/g solid for banana chips. while the equilibrium moisture content at 75% relative humidity at 30Â°C is -0.0537 g H2O/g solid in jackfruit chips, 0.01128 g H2O/g solid in pineapple chips and 0.0119 g H2O/g solid in banana chips. The Hasley equation model is the most suitable model to describe the water sorption isotherm phenomenon in jackfruit chips, while the Chen-Clayton equation model is suitable to describe the water sorption isotherm phenomenon in pineapple and banana chips products. The prediction of the shelf life of jackfruit and banana chips packed in nylon aluminum foil stored at 30Â°C with 75% RH is 2.6 months for jackfruit chips and 3 months for banana chips. While the prediction of the shelf life of pineapple chips packaged in metallized plastic paper is 4.2 months.